Com Laplanche, ler Marie Bonaparte: contribuições à psicanálise - Ribeiro, Sarug Dagir (Universidade Federal de Minas Gerais, 2021)
This thesis aims to review the notions of passive phallus (Bonaparte, 1967/1949), drilling complex (Bonaparte, 1952c) and the Lefebvre case (Bonaparte, 1952f / 1927) taking into account the Laplanchean method 'interpret [with] Freud' (Laplanche, 1988b) and the theory of generalized seduction. For this, three articles are developed in which new interpretations of the Bonapartean postulates are redesigned through this theoretical and methodological approach